Is there any truth in the myth that IVF treatments involve weight gain? - Saar-Ryss, Bozhena; Shilo, Michael; Friger, Michael; Grin, Leonti; Michailov, Yulia; Meltcer, Simion; Zaks, Svetlana; Rabinson, Jacob; Lazer, Tal; Friedler, Shevach (Frontiers in Reproductive Health, 2024)
Purpose To examine body weight change in women undergoing IVF-ET using antagonist protocol after up to three treatment cycles. Methods A prospective cohort study among IVF patients treated between 2018 and 2019. Each patient underwent weight measurement three times during the treatment cycle: before treatment, at the beginning of the hormonal stimulation and at the completion of the cycle, on the day of the pregnancy test. Data was also analyzed according to the BMI groups for normal weight, overweight and obese patients. Finally, weight changes were recorded following 519 treatment cycles, 240, 131 and 148 cycles for normal weight, overweight and obese patients. Results The change in the patient's weight was clinically non-significant either during the waiting period or during gonadotropin administration and overall, during the first, second or third cycle treatment. The recorded mean total weight change of 0.26±1.85, 0.4±1.81 and 0.17±1.7, after the first, second or third cycle treatment, represent a change of 0.36%, 0.56% and 0.23% of their initial weight after the first, second or third cycle treatment. This change of less than 1% of the body weight falls short of the clinically significant weight gain of 5-7%. Analyzing the data for the various BMI groups, the changes observed in body weight were under 1%, thus with no clinical significance. Conclusion The findings of the study reject the myth that hormone therapy involves clinically significant weight gain, and this can lower the concerns of many patients, candidates for treatment of ART.